Barriers to breast cancer screening among a sample of Egyptian females - Heba M. Mamdouh; Hazzem El-Mansy; Ibrahim F. Kharboush; Hanaa M. Ismail; May M. Tawfik; Mohamed Abdel El-Baky; Omnia G. El Sharkawy (Journal of Family and Community Medicine, 2014)
Background: Breast cancer (BC) is usually diagnosed in late stages in countries with limited resources. Early detection of BC is likely to improve the outcome of the disease for women in these areas. Objective: The aim of this study was to understand the possible personal, economic, and systems barriers to BC screening in a sample of Egyptian women. Materials and Methods: A cross-sectional study was conducted in family health centers representing the seven districts of Alexandria governorate, Egypt. A total of 612 women were randomly selected from the chosen centers. Results: In this sample of Egyptian women, the most frequently identified potential barriers to BC screening were the following: 81.8% would not seek care until they were ill, 77% were unwilling to have a mammogram until it was recommended by the doctor, 71.4% blamed the, lack of privacy, 69.2% thought that medical checkups were not worthwhile, and 64.6% blamed the cost of services. The study further revealed that women of lower education, women in the lower income category, women who did not do paid work, those who had poor knowledge of the risks of BC, and women with no family history of BC were more likely to perceive different screening barriers compared with their counterparts. Conclusion: Many potential personal, economic, and health system barriers were identified. Addressing these barriers by increasing the awareness of BC and dealing with the misconceptions that the women have can help the policy makers to design more culturally relevant strategies to motivate women to utilize screening services.